Dynamics of Three-Dimensional Pipes Conveying Fluid Using the Reissner Beam Theory - Anthony E. Muoka (2018)
The study of dynamics of pipes conveying ﬂuid has been the subject of research for many decades now, and various formulations, solution methodologies and applica-tions have been developed. The topic is well understood but research in this area is ongoing as the study of the subject is far from trivial. This is a classical model problem in the study of dynamics and stability of structures mainly because it is a physically simple system capable of displaying a wide array of interesting behaviour in both the linear and nonlinear regime. In this thesis, a geometrically exact fully implicit version of the 3D beam element, which employs the Rodrigues formula for the update of large rotations is used in the solution of the equations of motion. The nonlinear model for the ﬂexible beam conveying ﬂuid has been formulated and implemented to recover the interesting dynamic behaviour of the system in 3D. The advantage of this approach stems mainly from the fact that approach to engineer-ing problems depends upon the intended application, cost from a computational perspective, among other factors which may be taken into consideration, and this provides an alternative to existing approaches. Benchmark problems are presented in 2D and 3D, and conﬁrm robustness and accuracy of the formulation.